Nintendo Wii training on postural balance and mobility rehabilitation of adults with Parkinson's disease: a systematic review - Daniel Dominguez Ferraz; Karen Trippo; Adriana Dominguez; Adriana Santos; Jamary Oliveira Filho
Abstract Introduction: Postural instability affects balance control in Parkinson disease (PD) patients and increases the particular risk of falling compared with healthy older adults. Video games with not immersive virtual reality have been used in neurological disorders rehabilitation process. Objective: To evaluate the effectiveness of the video game console Nintendo Wii (NW) on postural balance and mobility treatment of adults with PD in Hoehn and Yahr stages I to III. Methods: The following databases were searched electronically on MEDLINE, Cochrane Library, PEDro, CAPES Periodic, BIREME, and LILACS databases. The search period for this review was January 2010 to June 2016. The assessment of methodological quality was performed using the PEDro Scale as reference. Results: 12 original studies were selected, but only 3 were randomized controlled trials (RCTs). Conclusion: Some of the studies analysed suggest that NW can provide improvement in balance and mobility of adults with PD. These benefits should be interpreted with caution because of the low methodological quality of the included trials, and the lack of common assessment of treatment effects. There is little evidence to ensure the effectiveness and support the inclusion of the treatment with NW of patients with PD.